Factors Influencing Sustainable Competitive Advantage During COVID-19 Pandemic: Role of Marketing and Innovative Capability - Christiarini, Renny; Yuwono, Wisnu; Hardianto, Hardianto (Jurnal EMT KITA, 2025)
COVID-19 pandemic has caused a great change regarding the perspective of global business but also driven fundamental changes in consumer behavior. This has caused initatives for companies to employ their own marketing strategy to achieve sustainable competitive advantage. In this study, researchers explore namely the correlation of spiritual marketing and entrepreneurial marketing on sustainable competitive advantage through the mediation of marketing capabilities and innovative capabilities. The research method utilized is quantitative one, with a data analysis approach through SMARTPLS, which is software for conducting SEM PLS testing, by conducting outer-inner modeling tests. The results of the study prove that there is a proceeded and significantly-positive influence regarding the spiritual and entrepreneurial marketing on sustainable competitive advantage. In addition, the marketing mediation capability variable has a significant direct correlation influence in shaping the sustainable competitive advantage, but innovative marketing capability does not show a significant influence on sustainable competitive advantage. The researcher also proves that marketing capability is able to mediate the influence of spiritual marketing and entrepreneurship on sustainable competitive advantage, meanwhile not for entrepreneurial marketing.